(untitled) (Ágora Journal, 2025)
The scarcity of visual records depicting enslaved Black individuals in the 19th century reflects both the technical limitations of the period and the historical erasure of these subjects. This absence carries multiple layers of complexity, including religious dimensions. Drawing on this understanding, we utilized one of the slave advertisements published in 19th-century newspapers, as analyzed by Freyre (1979), to develop a pilot representation using a generative artificial intelligence tool (Leonardo AI). The advertisement describes a woman identified as Teresa, including a reference to the pano-da-costa, which serves as a compelling indicator of her cultural and religious affiliations. This accessory, frequently referenced in contemporary imagery and texts, informed our efforts to create a post-indicial representation of Teresa. The resulting image aimed to align faithfully with her described attributes while ensuring a portrayal that was both respectful and humanized.